Use Of Hanging Ball Media to Increase Screen Kick Speed In Pencak Silat Sports - Akbar Fauzan Purnomo; Yosep Hamdalah; Mohammad Aulia; Dewi Susilawati (UNIVERSITAS NEGERI MAKASSAR, 2024)
Collecting the data under study was carried out according to the results of observations and findings of problems in the field in members of the extracurricular pencak silat at MI Assalam, North Sumedang District, Sumedang Regency. The problem found by researchers was the lack of speed in the sickle kick, so that extracurricular members lacked speed in performing the sickle kick which resulted in not being optimal in matches and movements. A sickle kick means doing a side kick with the body moving half a turn and kicking using the shin. The purpose of this study was to determine how much the use of hanging ball media accelerates the kick of the pencak silat sickle and the effect of using hanging ball media to accelerate the kick of the pencak silat sickle. Hanging ball media as a medium in right and left sickle kick exercises to make it easier for extracurricular members to do sickle kicks, because if you practice continuously using patching for a long period the legs of children aged 8-12 years are very vulnerable. This research method uses an experimental method with a pre-experimental design (one group pretest-posttest) and a relatively low pretest so that the practice is given 12 meetings and produces a posttest score that is obtained which results in a fairly good increase for the experimental group. After processing the data using the paired sample T-test, the value of sig (2-tailed) is 0.000.